Expression of RING Finger Protein 38 in Serotonergic Neurons in the Brain of Nile Tilapia, Oreochromis niloticus - Cham, Kai Lin; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Neuroanatomy, 2018)
Serotonin (5-hydroxytryptamine, 5-HT) is one of the major neurotransmitters modulating diverse behaviours and physiological functions. Really interesting new gene (RING) finger protein 38 (RNF38) is an E3 ubiquitin ligase whose function still remains unclear. A recent study has shown a possible regulatory relationship between RNF38 and the 5-HT system. Therefore, to gain insight into the role of RNF38 in the central 5-HT system, we identified the neuroanatomical location of 5-HT positive cells, and investigated the relationship between RNF38 and the 5-HT system in the brain of Nile tilapia, Oreochromis niloticus. Immunocytochemistry revealed three neuronal populations of 5-HT in the brain of tilapia; paraventricular organ (PVO), dorsal and ventral periventricular pretectal nuclei (PPd and PPv), and, superior and inferior raphe (SR and IR). 5-HT neuronal number was highest in the raphe (90.4 in SR, 284.6 in IR) followed by pretectal area (22.3 in PPd, 209.8 in PPv). Double-label immunocytochemistry showed majority of 5-HT neurons express RNF38 nuclear proteins (66.5% in PPd; 77.9% in PPv; 35.7% in SR; 49.1% in IR). These findings suggest that RNF38 could be involved in E3 ubiquitination in the central 5-HT system.